Congenital and acquired anomalies of the caudal vertebrae in dogs: Radiographic classification and prevalence evaluation - Paninárová, Michaela; Stehlík, Ladislav; Proks, Pavel; Vignoli, Massimo (Acta veterinaria Hungarica, 2016)
A prospective study to create radiographic classification of caudal vertebral anomalies in dogs was performed and the prevalence of the disorders estimated. Radiographic examination of the caudal vertebrae was performed in 595 client-owned dogs undergoing routine radiological examination of the hip joints. Anomalies of the caudal vertebrae were divided into four groups: (1) congenital anomalies with aberrant fusion of the vertebral epiphysis, like hemivertebra, block or transitional vertebra; (2) morphological anomalies like vertebra curva and dysplastic vertebral epiphysis; (3) post-traumatic changes, represented by fracture or luxation; and (4) degenerative changes, represented by spondylosis, osteophyte formation and mineralisation of intervertebral spaces. A total of 303 caudal vertebral anomalies were detected in 259 dogs (43.53% of all dogs examined). A single type of vertebral anomaly was present in 215 dogs and a combination of two pathologies was recorded in 44 dogs, which represents 83.01% and 16.99%, respectively, of the affected dogs. Congenital anomaly was present in 11.09% of the dogs examined. Sacrocaudal transitional vertebra was the most common congenital anomaly, present in 12.74% of the affected dogs. Radiographic examination of the caudal vertebrae is recommended as an essential part of any screening process to confirm the presence of congenital anomaly as a cause of kinked tail.
Keywords: Female; Animals; Dogs; mužské pohlaví; prospektivní studie; Prospective Studies; kink tail; Dog Diseases; ocas; psi; zvířata; Spine; ženské pohlaví; páteř; hemivertebra; nemoci psů; Tail; block vertebra; caudal vertebra; Male